Pendampinan Pengembangan Kawasan Wisata Lembang Karre Penanian, Kecamatan Nanggala Kabupaten Toraja Utara - Roland Salempang; Triani Sumule; Asriani Asriani; Nilasari Resky Pala’langan; Elisabeth Pali (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Tourism development in Lembang Karre Penanian, North Toraja Regency is one form of community service activities. PKM was held from February 17, 2021 to February 18, 2021. Activities consist of main activities, village activities, and additional activities. PKM activities aim to provide experience and as a learning process for students to explore village potentials that can be developed by the community. The method of implementing PKM at the location consists of survey activities, and planning additional activities in addition to the core activities that have been planned. Additional activities of PKM students received support from the local government and village communities. This is shown in the activities of PKM students involving many people from various groups.